Urban trading of medicinal plants in San Salvador de Jujuy (Argentina): How does species composition vary between different biocultural supply sites? - Acosta, Marina; Lambaré, Daniela Alejandra; Ladio, Ana H. (Ethnobiology and Conservation, 2021)
Studies related to the intrinsic biocultural variation of medicinal plant use in urban contexts are necessary for public health purposes. In this work we ask: What types of supply site offer medicinal plants in the pluricultural city of San Salvador de Jujuy? What are the most important medicinal plants commercialized in the city? How do species composition and their cultural importance vary between biocultural suppliers? The research followed an ethnobotanical approach and techniques, particularly participant observation, semi-structured and structured interviews with salespersons, and prior informed consent. We also identified plant material, considering the 10 plants most cited by the participants as having most commercial importance. Three types of medicinal plant supply site were identified: pharmacies, herbal stores and traditional informal sales stalls (informal vendors). Eighty-two medicinal species and two algal species were the most sold in this city. Total species richness differed between different types of biocultural supply site, herbal stores selling the highest richness (54 species), followed by informal vendors (43 species) and finally, pharmacies (36 species). The similarity index for the three sites revealed that herbal stores and informal vendors shared the highest number of species (46%). Through a GLM (generalized lineal model) we found that the supply sites most likely to sell native plants were the informal vendors. Despite the influence of global patterns of use, the supply sites varied in their intrinsic characteristics and offered different resources. Traditional informal vendors are fundamental to the Jujuy population for the supply of unique native species. This phenomenon has marked consequences for public health, highlighting the essential biocultural role played by this supply point in maintaining the traditional Andean health system.